Implementing the Merdeka Curriculum: Adapting CLT for Innovative ELT Practices in the Context of Indonesia’s Merdeka Curriculum - Sujariati Sujariati; Risman Wanci; Rampeng Rampeng (Soegijapranata Catholic University, 2025)
This study explores how Communicative Language Teaching (CLT) approaches are adapted to support innovative English Language Teaching (ELT) practices within the framework of the Merdeka Curriculum in Indonesia. It also investigates the challenges English teachers face in implementing the curriculum, how they perceive and apply CLT-based methods in relation to its student-centered, competency-based orientation, and how students perceive English language learning under the Merdeka Curriculum. Employing a qualitative research design, data were collected through classroom observations, semi-structured interviews with 20 English teachers across four provinces, and 15 students of secondary school. Data were analyzed using an interactive model by (Miles at al., 2014) and which include three main components: data reduction, data display, and conclusion drawing/verification, and inductive coding approach to identify recurring pedagogical patterns, contextual adaptations, and teacher/student perspectives. Findings reveal that teachers decontextualize CLT through four key strategies: localizing communicative tasks, integrating project- and inquiry-based learning, redefining teacher roles, and utilizing low-tech digital tools. However, systemic and classroom-level challenges persist, including limited curriculum understanding, insufficient professional development, and unequal access to resources, assessment misalignment, and classroom management difficulties. While teachers generally perceive CLT as compatible with Merdeka’s aims, its implementation remains partial due to institutional and logistical constraints. Student perceptions indicate that many enjoy communicative, interactive, and project-based learning more than traditional methods. However, some experience anxiety due to limited English skills and lack of familiarity with student-centered activities. The study implies that successful implementation of the Merdeka Curriculum requires not only curricular reform but also continuous teacher support, student readiness programs, and the development of contextually appropriate assessment practices